A model of repression: CTD analogs and PIE-1 inhibit transcriptional elongation by P-TEFb - Zhang, Fan (Cold Spring Harbor Laboratory Press, 2003)
The positive transcription elongation factor b (P-TEFb) contains cyclin T1 (CycT1) and cyclin-dependent kinase 9 (Cdk9). For activating the expression of eukaryotic genes, the histidine-rich sequence in CycT1 binds the heptapeptide repeats in the C-terminal domain (CTD) of RNA polymerase II (RNAPII), whereupon Cdk9 phosphorylates the CTD. We found that alanine-substituted heptapeptide repeats that cannot be phosphorylated also bind CycT1. When placed near transcription units, these CTD analogs block effects of P-TEFb. Remarkably, the transcriptional repressor PIE-1 from Caenorhabditis elegans behaves analogously. It binds CycT1 via an alanine-containing heptapeptide repeat and inhibits transcriptional elongation. Thus, our findings reveal a new mechanism by which repressors inhibit eukaryotic transcription.